2020
DOI: 10.5709/acp-0295-7
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on How Inhibition in Cognitive Processing Contributes to Fluid Reasoning

Abstract: This article reports an investigation of how inhibition contributes to fluid reasoning when it is decomposed into the reasoning ability, item-position, and speed components to control for possible method effects. Working memory was also taken into consideration. A sample of 223 university students completed a fluid reasoning scale, two tasks tapping prepotent response inhibition, and two working memory tasks. Fixed-links modeling was used to separate the effect of reasoning ability from the effects of item-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…The path coefficients from inhibition ( β = −.11) and shifting ( β = −.08) to Gf were not significant. On the other hand, recent studies suggested that there were significant correlations between shifting ( Wang et al 2013 ) and inhibition ( Wang et al 2020 ) with Gf when EFs were represented by a different approach.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The path coefficients from inhibition ( β = −.11) and shifting ( β = −.08) to Gf were not significant. On the other hand, recent studies suggested that there were significant correlations between shifting ( Wang et al 2013 ) and inhibition ( Wang et al 2020 ) with Gf when EFs were represented by a different approach.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, there have been considerable debates as to whether inhibition (or attention control) is related to WMC (e.g., Draheim et al 2020 ; Rey-Mermet et al 2019 ; Unsworth et al 2020 ; Wang et al 2020 ). On one hand, a large body of studies suggest a moderate to high correlation between inhibition and WMC ( Draheim et al 2020 ; Unsworth et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%